Dilemma Behind Post-Spinal Tetraplegia: Is Conversion Disorder Really the Culprit? - Nasreen, Farah; Khalid, Atif; Siddiqui, Sobia Manaal; Ahsan, Mohd (International Journal of Human and Health Sciences (IJHHS), 2022)
The occurrence of intra-operative conversion disorder with tetraplegia in a patient undergoing emergency appendectomy under spinal anaesthesia has been described in this case report. A 19-year-old female patient was given spinal anaesthesia for an emergency appendectomy. She had a block up to the T10 level as per assessment. Following confirmation of sensory and motor blockade level, the patient became apnoeic and appeared to stop responding abruptly. Her vitals remained constant except for tachycardia. She was taken on bag and mask ventilation and preparation for endotracheal intubation was underway. The patient began to respond again after a few minutes of continual stimulation and bag mask ventilation. Rest of the perioperative period was uneventful. Postoperative psychiatry consultation was done, and she was diagnosed as a case of conversion disorder. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 332-334